The breadth of success and failure factors with PPPs implementation - Ncedo Cameron Xhala; Juraj Nemec; Kahilu Kajimo-Shakantu (European Financial and Accounting Journal, 2017)
The financing of public infrastructure investment through public-private partnerships faces daunting challenges related to the success of implementation of public infrastructure investment. There are multi-dimensional competing factors which inhibit the short and long-term implementation of PPPs, some of them may result to failure of implementation. The implementation of PPPs requires a set of success factors and its positive result is not automatic. This paper offers an overview of challlenges facing the implementation of PPPs and lists the most important success factors which increase the chance for successful implementation of PPPs. This paper further explores the range and ranking of the most important successful factors required for the realization of PPPs.
Keywords: H89; 650; Investment; Public Infrastructure